Bros [videorecording (DVD)] - Stoller, Nicholas; Eichner, Billy, 1978-; Eichner, Billy, 1978-; MacFarlane, Luke; Bearse, Amanda, 1958-; Branum, Guy, 1975-; Díaz, Guillermo, 1975-; Fierstein, Harvey, 1952-; Jones, Dot Marie; Lawrence, Miss, 1982-; Lindley, Eve; Ts Madison; et al. (Universal Studios, 2022)
Bobby is a struggling podcast host who hates commitement. That all changes when he meets Aaron, a detached lawyer who likes to play the field. Repeatedly drawn to each other, both men begin to show their vulnerable sides as their undeniable attraction turns into something resembling a commitment.